2021
DOI: 10.1080/02656736.2021.1892837
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and recommendations for magnetic hyperthermia characterization measurements

Abstract: Purpose: The localized heating of magnetic nanoparticles (MNPs) via the application of time-varying magnetic fieldsa process known as magnetic field hyperthermia (MFH)can greatly enhance existing options for cancer treatment; but for broad clinical uptake its optimization, reproducibility and safety must be comprehensively proven. As part of this effort, the quantification of MNP heatingcharacterized by the specific loss power (SLP), measured in W/g, or by the intrinsic loss power (ILP), in Hm 2 /kgis frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…One of the main limitations for the critical analysis of MHT measurements is how to determine the heating power of MNPs [ 71 ]. The Specific Absorption Rate (SAR) is an empirical parameter frequently used by radiological protection departments to regulate the amount of radiation absorbed by patients when exposed to radiofrequency fields and it is normalized to the mass of biological tissue irradiated in terms of W/g [ 72 ].…”
Section: Physical Concepts Of Magnetic Hyperthermia (Mh)mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main limitations for the critical analysis of MHT measurements is how to determine the heating power of MNPs [ 71 ]. The Specific Absorption Rate (SAR) is an empirical parameter frequently used by radiological protection departments to regulate the amount of radiation absorbed by patients when exposed to radiofrequency fields and it is normalized to the mass of biological tissue irradiated in terms of W/g [ 72 ].…”
Section: Physical Concepts Of Magnetic Hyperthermia (Mh)mentioning
confidence: 99%
“…This model predicts a linear dependence of the SAR on the frequency and a quadratic dependence on H, although this is only valid for highly anisotropic MNPs and a small H, and thus, it cannot be assumed as a universal parameter. Besides, recent double-blind experiments showed that the specific features of the experimental set-ups and the thermal curves analysed may produce inconsistent SAR values between laboratories [ 71 ]. A promising solution to achieve a global and consistent parameter to determine heating power is to measure the high frequency magnetic loop of the MNPs [ 76 ].…”
Section: Physical Concepts Of Magnetic Hyperthermia (Mh)mentioning
confidence: 99%
“…The magnetic fluid hyperthermia is a well-known method that takes advantage of the heat released by magnetic nanoparticles when subjected to radiofrequency fields; the heat released leads to cancer cell apoptosis or necrosis and, consequently, it is an appropriate method for the treatment of tumours 1 . The deep comprehension of the influence of the nanoparticle properties, colloidal media as well as the frequency and amplitude field range is relevant to optimizing the conditions for future successful clinical applications [2][3][4] . Ac-calorimetry is the most common technique for the characterization of the heating efficiency; however, the most recent ac magnetometry methods 5,6 has been proven to be a very useful tool to obtain valuable information about the magnetic properties of the dynamic systems, which is not accessible from the calorimetric measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the effect of the nanoparticle size on the heating capacity of a suspension of MNPs under an alternating magnetic field is expected to increase as particle size increases, although many other factors can mask this result due to collective behavior forming chains, for example, and poor colloidal stability, which can lead to huge errors due to the precipitation of nanoparticles ( Figure S2 ). Such sample degradation issues complicate the comparison between different MNPs and equipment [ 26 ]; however, experimental data in the literature have shown SAR values between 20 and 65 W/g (40 kAm −1 , 77 kHz) for samples synthesized by thermal decomposition in 1-octadecene, with the same mean size (14 nm) but different size distribution [ 27 ]. The highest SAR was closer to the data reported here under similar field conditions and was associated with the sample with the narrowest size distribution.…”
Section: Resultsmentioning
confidence: 99%